Using of numerical modeling for verification of the functional hypothesis - Sokolovsky, A.I.; Chelbaevsky, Z.Yu. (Вопросы атомной науки и техники, 2007)
One-dimensional harmonic oscillator in a quasi-equilibrium medium which consists of non-interacting harmonic oscillators has been considered. Kinetic equation for this Brownian particle has been derived on the basis of the Bogolyubov functional hypothesis. Solution of the kinetic equation was numerically compared with an exact solution obtained by Bogolyubov. The results of this comparison are presented in a simple graphic form. Розглянуто одновимірний гармонічний осцилятор у квазірівноважному середовищі, яке складається з гармонічних осциляторів, що не взаємодіють. На основі функціональної гіпотези Боголюбова одержано кінетичне рівняння для цієї броунівської частинки. Розв’язок кінетичного рівняння чисельно порівняно з точним розв’язком, одержаним Боголюбовим. Підсумки порівняння представлені в простій графічній формі. Рассмотрен одномерный гармонический осциллятор в квазиравновесной среде, которая состоит из невзаимодействующих гармонических осцилляторов. На основе функциональной гипотезы Боголюбова получено кинетическое уравнение для этой броуновской частицы. Решение кинетического уравнения численно сравнено с точным решением, полученным Боголюбовым. Результаты сравнения представлены в простой графической форме.